UWSP: sleeping algorithms for underwater sensor network - Lu HONG; Feng HONG (Tongxin xuebao)
Sleeping scheme is one of the key means of saving energy for wireless sensor network. However, existing MAC protocols for underwater sensor network (UWSN) mainly focus on maximizing throughput but ignore sleeping schemes. Moreover, in existing sleeping schemes nodes wake up rapidly, which will loss the life of hardware, waste en-ergy to open/close circuits, and increase collision probability. So, a tree topology based sleeping algorithm for UWSN was proposed, which utilizes the special characteristics of underwater acoustic channel. This algorithm could reduce wakeup frequency, prolong sleeping time and keep the end to end delay from being affected by sleeping time. This algo-rithm has no collision and no channel reservation and its usability and capability have been verified by simulation meth-ods.